Effects of the Four-Herb Compound ANBP on Wound Healing Promotion in Diabetic Mice. (December 2015) - Hou, Qian; He, Wen-Jun; Chen, Li; Hao, Hao-Jie; Liu, Jie-Jie; Dong, Liang; Tong, Chuan; Li, Mei-Rong; Zhou, Zhong-Zhi; Han, Wei-Dong; Fu, Xiao-Bing
Wound healing is a troublesome problem in diabetic patients. Besides, there is also an increased risk of postsurgical wound complications for diabetic patient. It has been revealed that traditional Chinese medicine may promote healing and inhibit scar formation, while the changes of morphology and physiology of wounds on such medicine treatment still remain elusive. In this study, we first used the ultralow temperature preparation method to produce mixed superfine powder from Agrimonia pilosa (A), Nelumbo nucifera (N), Boswellia carteri (B), and Pollen typhae (P), named as ANBP. Applying ANBP on 40 streptozotocin (STZ)-induced diabetic C57BL/6 mice (4-6 weeks, 20 ± 2 g), we observed that the wound healing process was accelerated and the wound healing time was shortened (14 days, P < .05). Pathological observation using hematoxylin–eosin staining indicated that inflammatory cells were reduced ( P < .05) while the thickness of granulation tissue and length of epithelial tongue were increased ( P < .05). The vascular density was increased on 7 and 14 days after ANBP treatment. Masson and Sirius red staining showed that, at the early stage of trauma, the expressions of Col I and Col III, especially Col III, were increased in the ANBP group ( P < .05). Studies in vitro demonstrated that tubular formation was significantly increased after ANBP treatment on human vascular endothelial cells in a dose-dependent way. Taken together, our studies revealed that ANBP treatment could accelerate wound healing, promote vascularization, and inhibit inflammation, suggesting the potential clinic application of ANBP for diabetes mellitus and refractory wounds.